2017
DOI: 10.33549/physiolres.933798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perivascular Adipose Tissue on Arterial Adrenergic Contractions in Normotensive and Hypertensive Rats With High Fructose Intake

Abstract: The aim of this study was to investigate the effect of high fructose intake associated with moderate increase in adiposity on rat arterial adrenergic responses and their modulation by perivascular adipose tissue (PVAT). After eight-week-lasting substitution of drinking water with 10 % fructose solution in adult normotensive Wistar-Kyoto rats (WKY) and spontaneously hypertensive rats (SHR), their systolic blood pressure, plasma triglycerides, and relative liver weight were elevated when compared to their respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…In our study, we confirmed that the long-lasting increase in fructose treatment did not affect the maximal force of adrenergic contraction but increased the sensitivity of adrenergic receptors to exogenous noradrenaline and significantly reduced endothelium-dependent vasorelaxation, although did not alter relaxation to NO donors (Figure 3a-d). Similar findings were observed by Zemancikova et al (2014) [7], who reported an unchanged adrenergic contraction but decreased acetylcholine-induced vasorelaxation in the thoracic aorta of normotensive Wistar rats drinking 10% fructose solution. Moreover, they pointed out that fructose did not induce cardiovascular alterations in rats without a functional NO system in the state of NO deficiency (induced by N G -nitro-L-arginine methylester (LN) administration).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, we confirmed that the long-lasting increase in fructose treatment did not affect the maximal force of adrenergic contraction but increased the sensitivity of adrenergic receptors to exogenous noradrenaline and significantly reduced endothelium-dependent vasorelaxation, although did not alter relaxation to NO donors (Figure 3a-d). Similar findings were observed by Zemancikova et al (2014) [7], who reported an unchanged adrenergic contraction but decreased acetylcholine-induced vasorelaxation in the thoracic aorta of normotensive Wistar rats drinking 10% fructose solution. Moreover, they pointed out that fructose did not induce cardiovascular alterations in rats without a functional NO system in the state of NO deficiency (induced by N G -nitro-L-arginine methylester (LN) administration).…”
Section: Discussionsupporting
confidence: 90%
“…However, according to other available studies, the question of a direct association of high fructose consumption with an increase in blood pressure represents a controversial issue. Chronic fructose administration significantly elevated SBP in normotensive conditions [ 1 , 7 , 15 ]; on the other hand, some authors found no impact of this treatment on blood pressure [ 16 , 17 ]. In our study, although we revealed a significant effect of the eight-week fructose administration on the values of systolic blood pressure, there were no differences between the experimental groups in individual weeks ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concerning the differences in PVAT between SHR and WKY rats, qualitative distinctions seem to be more important than the quantitative ones [29]. To support this concept, in our previous study, we have demonstrated that moderate increase in body adiposity potentiates the anticontractile effect of PVAT in normotensive WKY rats but not in SHR [15]. Therefore, it is evident that SHR have qualitatively different PVAT, and the increase in amount of this tissue might not cause its larger anticontractile effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the impairment in anticontractile action of mesenteric arterial PVAT was detected also in spontaneously hypertensive rats (SHR), which are characteristic by lower body weight comparing to normotensive Wistar-Kyoto rats [12], and this defect in PVAT was shown to be associated with the exaggerated sensitivity of SHR arteries to vasoconstrictors [13, 14]. Moderate growth in adipose mass due to high fructose intake potentiated the anticontractile properties of PVAT in normotensive rats but it did not improve them in SHR, indicating that qualitative rather than quantitative changes of PVAT are important when considering its participation in increased vascular tone in SHR [15].…”
Section: Introductionmentioning
confidence: 99%